Euroscepticism : party politics, national identity and European integration - Harmsen, Robert; Spiering, M. (Menno) (European studies (Amsterdam, Netherlands), 2004)
The accelerated pace of European integration since the early 1990s has been accompanied by the emergence of increasingly prominent and multiform oppositions to the process. The term Euroscepticism has appeared with growing frequency in a range of political, media, and academic discourses. Yet, the label is applied to a wide range of different, and occasionally contradictory, phenomena. Although originally associated with an English exceptionalism relative to a Continental project of political and economic integration, the term Euroscepticism is now also identified with a more general questioning of European Union institutions and policies which finds diverse expressions across the entire continent. This volume of European Studies brings together an interdisciplinary team of contributors to provide one of the first major, multinational surveys of the growth of these Eurosceptic tendencies. Individual chapters provide detailed examinations of developments in France, Germany, the Netherlands, the United Kingdom, Ireland, Sweden, Austria, the Czech Republic, Poland, and Switzerland. Overall, the volume draws a distinctive portrait of contemporary Euroscepticism, situating the phenomenon not only relative to the progress of European integration, but also in relation to broader questions concerned with the evolution of party politics and the reshaping of national identities.